Tinjauan Hadis Terhadap Tradisi Uang Panai dalam Adat Pernikahan Bugis-Makassar (Analisis Isi Hadis dalam Film Uang Panai Maha(r)l) - Fitra, Muh. Naufal; Nasrulloh, Nasrulloh; Syafni, Hafidhah; Tamam, Muhammad Ibnu (LP2M IAIN Palopo, 2024)
The tradition of uang panai is one of the traditions that is still preserved by the Bugis-Makassar community in marriage. This tradition is in the form of a sum of money the groom gives the bride as a sign of appreciation and seriousness to marry her. However, the tradition of uang panai represented in the movie “Uang Panai Maha(r)l” shows a shift in value and is not based on Islamic values contained in the sources of Islamic law, namely the Al-Quran and Hadith. This study aims to analyze the content of hadith about the tradition of uang panai in Bugis-Makassar marriage customs represented in the film “Uang Panai Maha(r)l”. This research uses a descriptive qualitative method with a qualitative content analysis technique. The results showed that the hadiths related to marriage do not contradict the tradition of uang panai as long as they are by Islamic teachings. However, the concept of uang panai in the movie “Uang Panai Maha(r)l” is depicted excessively and contains elements of coercion. Thus, the concept of uang panai in the movie is not by the meaning of the hadith, which recommends making it easier for each other to carry out marriage and walimah. Based on the results of this study, it can be concluded that the tradition of uang panai in Bugis-Makassar wedding customs can be justified if it is carried out by Islamic teachings, namely the recommendation of marriage, the recommendation of facilitating marriage, and the recommendation of organizing walimah. This tradition must be carried out wisely and does not contain elements of coercion. Keywords: Uang Panai, Hadith, Bugis-Makassar Wedding, Film